Kritik Pervez Hoodbhoy terhadap Islamic Science - Shohibul Mujtaba, Muhammad; Setyo Rahmawati, Zakiya; Heelmafika, Dheehan (Institut Agama Islam Ngawi, 2023)
Abstract: One of the prominent Islamic scientists who reject and criticize the development of Islamic science is Pervez Hoodbhoy. He said that the Qur'an is not a scientific book, even though it explicitly discusses various natural events. Therefore, in this article, the author will discuss the criticism of the scientist Pervez Hoodbhoy in Islamic Science. And examines the reasons for criticism and rejection as well as the responses of several other Islamic scientists to Pervez Hoodbhoy's criticism. by using a qualitative approach, which is library research. The research results show that, Hoodboy's greatest error in understanding Islamic science was first his belief that science is secular while acknowledging the existence of divinity; second, he stated that attempts to create Islamic sciences would fail because knowledge from the West raises doubt and prediction to scientific degrees in terms of methodology; third, morality and theology in any way will not be able to create new science; and fourth, there is no definition of science. Fourth, there is no acceptable definition of science among Muslims. fifth, there is only one universal science on the globe. Sixth, religion and science have different research dimensions. Seventh, questions regarding Islamic Science in the Middle Ages, and eighth, Muslim-developed doubts about Islam's character in science. Keywords: Criticism, Islamic Science, Pervez Hoodbooy Abstrak: Pervez Hoodbhoy adalah salah satu tokoh ilmuwan islam yang menolak dan mengkritik pengembang islami sains. Ia menyatakan bahwa Al Qur’an bukan sebagai kitab sains walaupun secara eksplisit membahas berbagai peristiwa alam. Oleh karena itu, artikel ini bertujuan untuk mengkritik pemikiran ilmuwan Pervez Hoodbhoy terhadap Islamic Science. Penelitian ini menggunakan pendekatan kualitatif yang bersifat library research. Hasil penelitian menunjukkan bahwa kesalahan terbesar Hoodboy dalam memahamai sains Islam adalah pertama, pemikirannya bahwa sains bersifat sekuler padahal ia mengakui eksistensi ketuhanan, kedua, ia menyatakan bahwa usaha untuk menciptakan sains Islam akan gagal karena pengetahuan dari barat mengangkat keraguan dan pendugaan ke derajat ilmiah dalam hal metodologi, ketiga, prinsip-prinsip moral dan teologi betapapun tidak akan mampu menciptakan sains baru, keempat, belum ada definisi sains yang dapat diterima kaum muslimin, kelima, hanya ada satu sains di dunia ini dan bersifat universal, keenam, agama dan sains memiliki dimensi penelitian yang berbeda, ketujuh, keraguannya terhadap ilmu pengetahuan Islam di abad pertengahan, dan kedelapan, keraguannya akan karakter Islam dalam sains yang dikembangkan oleh muslim. Kata Kunci: Kritik, Sains Islam, Pervez Hoodbooy